Financial distress of the PN17 Companies / Norizyanie Bad Hamid - Bad Hamid, Norizyanie (2011)
The purpose of this study is to determine the factor determinant the companies financial distressed by using the multiple regression and Pearson correlation to indetifying the factor determinant the companies financial distressed. Besides that this study using 26 sample of distressed companies in PN17 companies that listed in Bursa Malaysia by analysing all their ratio from their 5 years annual report which is from 2005 until 2006. Among all the 16 ratio has been examined, there are 5 ratio has significant relationship as the factor that determinant the financial distressed which is debt ratio, time interest earned, cash turnover, return on asset and return on equity.